Therapeutic methods in Age-Related Macular Degeneration: Recent advances and future perspectives (Research, Society and Development, 2025)
This study aims to conduct an integrative literature review, mapping established and emerging therapeutic approaches for age-related macular degeneration (AMD), with a special focus on clinical effectiveness, cost-effectiveness, and feasibility of implementation in public health systems. This research investigated available and emerging therapies for AMD, emphasizing clinical efficacy, treatment durability, and incorporation into public policy. The analysis highlighted traditional antiangiogenic agents such as ranibizumab and aflibercept, while discussing their limitations regarding cost and access. Emerging agents like faricimab and OPT-302 were identified as promising due to longer intervals between applications. In addition, innovative therapies such as cell and gene therapy showed potential to modify the course of the disease, especially in advanced cases. The study reinforces the importance of considering equity in access to treatments and the need for evidence-based public health policies. The abstract concludes by emphasizing the relevance of further studies to strengthen the clinical effectiveness, cost-effectiveness, and real-world applicability of the most modern therapeutic approaches.